(untitled) (Research, Society and Development, 2023)
Objective: To report a health education action, where an action was carried out with the purpose of studying the knowledge and guidance on the students of a private institution to promote the health of indigenous peoples. Method: private nursing was for five academic semesters of the seventh and sixth semesters of a University of the State of Pará. An activity was developed for the studies and guidance of students in the first semester of continuing education on health promotion for indigenous peoples. This was followed by a dynamic where the discs answered questions about the subject, through an online platform. Result: The educational action recognized that the students have prior knowledge of the academic subject, and it was understood that they have in their related curriculum note. Conclusion: It was observed that the students had a brief knowledge of the subject addressed.